Current Status Of Termites as Pest of Bamboos and their Control - Thakur, M. L. (Indian Forester, 1988)
Although bamboo consitute the single most important forest produce, unfortunately, very little attention has been paid to the understanding of their pest complex Entomologically, bamboos have never been considered as an important crop, therefore, it is not surprising that very little work has been done in India on this aspect, particularly regarding pests of green bamboo. This paper reviews the available information on status of termites as pest of bamboos in forest nurseries, plantations as well as harvested bomboos under storage conditions. Control measures currently in vogue, have been discussed at length.